Las enmiendas de participación ciudadana: su inserción en el procedimiento legislativo ordinario de Les Corts Valencianes (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2017)
Since 2015, public hearings and citizen´s amendments are part of the participation of the legislative procedure in the regional Parliament of Valencia (Corts Valencianes). The citizen´ amendments are a common trigger for a new connection between Parliament and citizenship.
Keywords: Trasparency; amendments; legislative procedure